Palm Kernel Shell as a Source of Functional Biochar: A Review of Recent Scientific Progress - Margareta N. Cahyanti; Dewi K.A. Kusumahastuti; Sri Hartini (Jurnal Penelitian Pendidikan IPA, 2025)
This report examined the research trends in production and application of biochar derived from palm kernel shells (PKS) over the past decade. A Systematic Literature Review (SLR) was conducted on 63 articles indexed in Scopus between 2015 and 2025, with bibliometric mapping performed using VOSviewer. From 2015, the number of publications on PKS biochar grew gradually, reaching a peak in 2020 and 2023.  Through the use of keyword co-occurrence mapping, four significant clusters of PKS biochar research were identified. These clusters primarily dealt with pyrolysis, activated carbon, biofuels, and biomass usage as main themes.  The term "biochar" has a critical function in connecting applications pertaining to agriculture, the environment, and energy, as seen by its core positioning and strong keyword connections across clusters.  Su Shiung Lam and Rock Keey Liew (Universiti Malaysia Terengganu) have the strongest collaboration link (strength 17), according to the VOSviewer study, which is supported by 6 documents and 640 citations.  Based on the number of publications, Malaysia is the leader in PKS biochar research with 33, followed by Thailand with 8 and Indonesia with 6. The findings of this study can serve as a useful reference for researchers and institutions looking to understand current trends, active contributors, and major themes in PKS biochar research.